A new species of Alpheus (Crustacea, Decapoda, Alpheidae) from the Arabian Sea, Kerala, India - de Grave, Sammy; Krishnan, Apsara S.; Kumar K. P., Anil; Christodoulou, Magdalini (Zootaxa, 2020)
A new species of Alpheus, A. samudra nov. sp., is described from the bycatch of trawlers operating between 275–375 m depth on the Quilon Bank (Kerala, India). The new species belongs to the brevirostris group, but can be easily distinguished from all but one species, by the extremely laterally compressed major cheliped. Alpheus samudra nov. sp. is very similar to A. leptocheles Banner & Banner, 1975 in the form of the major cheliped, but the proportions of the fingers to the palm and the shape of the fingers easily separate both species.